Steam System Optimization at Palm Oil Mill: Case Study in Sabah, Malaysia - Mohd Danial, Ibrahim; S.A., Najamudin; S.S., Lam (Qazvin, Iran : Qazvin Islamic Azad University, 2022)
In this paper, a preliminary study of industrial steam system reveals that most of the industrial steam user especially the palm oil mill did not bother to save energy as long as the mill meets their productions target and is getting profits for the company. The management is not aware that a huge amount of energy is being wasted during the processes of extracting oil from the fresh fruit bunch (FFB). To embark this study, Steam System Scoping Tool (SSST), Steam System Assessment Tool (SSAT) and 3E Plus: Insulation Program Software, provided by the United Nations Industrial Development Organization (UNIDO) are used to assess the efficiency of steam system operations. The tools also assist in preliminary assessments of how efficiently the steam system is operating. After analyses are conducted, the proposed improvement project is recommended to modify the system back to its initial designed best efficiency. The results also show that there were various losses that are contributing to the energy waste and its cost impact to the mill. Meanwhile, the boiler efficiency was only about 68.6%. The findings proposed steam system optimization (SSO) opportunities by installing the feedwater economizer and reducing the blowdown rate of the boiler. The efficiency of the boiler was increased to 77% from its current operating condition. This also improved the steam quality and production output of the mill. Through these SSO, the annual demand saving is around 4.9 MW, with an energy saving of 75,276 GJ/yr., capable of reducing 13,002 metric tons of carbon dioxide emissions per annum and save 598.3 Tph/yr of biomass fuel. Thus, through this steam system optimization the estimated annual net cost savings are around USD 100,000.00. This paper aims at promoting similar system optimization projects at other plants throughout Malaysia, as it benefits to all industrial steam user especially the palm oil mill industries in Malaysia.